Análise do nível de obstrução em gotejadores operando com diluições de água produzida tratada - Hudson, Salatiel Marques Vale (Universidade Federal Rural do Semi-Árido, 2019)
The water produced represents the largest volume of liquid effluent from the oil production activities. Because of the shortage of water in the Brazilian semiarid region, the use of this effluent in agriculture through drip irrigation system can become an effective strategy for the region. However, the vulnerability of drippers to clogging should be taken into account and may be mitigated by the dilution technique in water. In this context, this study aimed to analyze the performance hydraulic units gotejadoras by applying diluitions of produced water treated in underground water. For that, five experimental stands were set up in an experimental area of the Laboratory of Rural Constructions and Ambience, located in the East Campus of the Universidade Federal Rural do Semi-Árido, Mossoró-RN. To evaluate the hydraulic performance and detection of the level of clogging of the drippers by applying produced water treatment (PW) diluted in underground water (UW) for 160 h, a completely randomized experiment (DIC) was set up in a subsubdivided, with three replicates; having in the plots the five treatments T1 - 100% UW; T2 - 90% AS and 10% PW; T3 - 80% UW and 20% PW; T4 - 70% UW and 30% PW and T5 - 60% UW and 40% PW, in the subplots the three types of non-self-compensating drippers (G1 - 1,6 L h-1, G2 - 1,6 L h-1 and G3 - 1,7 L h-1 and in the subsubparcels the evaluation times (0, 40, 80, 120 and 160 h) of the effluent distribution uniformity. The following hydraulic performance indicators were evaluated every 40 h: flow (Q), relative flow (QR) and coefficients relative flow reduction (RQR), distribution uniformity (CUD), flow variation (CVQ) and statistical uniformity (Us). At the same time, physical-chemical analyzes of the dilutions of treated produced water were made. After 160 h, a second experiment was set up to obtain the flow versus service pressure curves for each drip model. Statistical analysis of the data was carried out using the statistical software System for Statistical Analysis Version 9.1. Among the physico-chemical characteristics of the dilutions, only pH represented a severe risk of drip obstruction, while the attributes CE, Ca2+, Mg2+, SS and SD represented a risk of obstruction classified as low. The linear, quadratic and square root regression models were the ones that best fit the relationship between the hydraulic performance variables Q, QR, RQR, CUD, CVQ and Us, as a function of the operating time of the irrigation units. The linear and quadratic regression models were better fitted to the flow variable (Q), as a function of the position of the drippers along the lateral lines. The highest susceptibility to clogging was verified for G2 dripper, when submitted to T5 treatment (60% UW and 40% PW), probably due to its smaller filtration area and the formation of scale on it. The G2 dripper, even operating under the recommended maximum pressure (100 kPa), has not reached the nominal flow rate reported by the manufacturer, which may compromise system performance. The G3 dripper, when submitted to T1 (100% UW) treatments to T3 (80% UW and 20% PW), is the most recommended in the operation with diluted treated water
Keywords: Emissores; Entupimento; Petróleo; Reuso; Emitters; Clogging; Oil; Reuse; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO